Africa?s Growing Role in World Politics - Deych, Tatiana; Deych, Tatiana (MeaBooks Inc, 2016)
This volume, titled ?Africa?s Growing Role in World Politics,? includes a selection of papers dedicated to the problems of the contemporary international relations and foreign policies of the African states. Most of these papers were presented at the panels, held within the framework of the 13th International Conference of Africanists ?Society and Politics in Africa: Traditional, Transitional and New? (Moscow, Russia, May 27?30, 2014). The book contains many articles devoted to the Western countries? policies in Africa. On the background of the ongoing competition between Washington and Beijing, the US Administration has recently increased the amount of attention it pays to the continent. European Union is also actively developing its strategic partnership with Africa. The authors analyze thoroughly the ongoing cooperation between African states and a great ?emerging donor? and investor ? China. They particularly address the question about possible implications of China?s African policy for the countries of the continent. Major attention is given to Sudan and South Sudan. One of the urgent problems addressed by this book is the situation with African IDPs and refugees, their life conditions in camps and the measures for their transition to normal life.